Modern pastry and plated dessert techniques - British Columbia Cook Articulation Committee; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2014)
"Modern Pastry and Plated Dessert Techniques is one of a series of Culinary Arts books developed to support the training of students and apprentices in British Columbia's food service and hospitality industry. Although created with the Professional Cook and Baker programs in mind, these have been designed as a modular series, and there for can be used to support a wide variety of programs that offer training in food service skills."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Pastry -- Textbooks; Desserts -- Textbooks; Electronic books